Mapping and candidate gene identification of loci induced by phytohormones in barley (Hordeum vulgare L.) - Tocho, Erica Fernanda (2014)
Phytohormones, a group of structurally unrelated small molecules are plant-signalling compounds that trigger induced resistance against certain pathogens and herbivores. The hormones jasmonic acid (JA), ABA, salicilic acid (SA) and ethylene (ET) are known to play major roles in regulating plant defence responses. In order to determine the changes in growth and in the chlorophyll content induced by the exogenous application of these elicitors, a set of DH lines of the Oregon-Wolfe Barley mapping population, previously screened to locate aphid resistant genes, was investigated. The aim of the current research was to map the induced defence genes and to reveal the relationship with aphid resistance. There were highly significant differences between controls and hormone treated plants in the aerial fresh and dry weights (AFW, ADW), the foliar area (FA) and the root dry weight (RDW). More than 15 JA and ET-induced lines exceeded the chlorophyll (Ch) values of their controls. Most of the plant traits were associated with the same genetic windows on chromosomes 3H, 5H and 7H in the controls and hormone treated plants. QTL(s) identified on chromosome 3H and 5H explained most of the variation of AFW, ADW, FA and RDW of controls and treated plants. QTL(s) located on chromosome 5H were associated with the variation of chlorophyll contents on JA-treated plants. The Ch in ET and ABA-treated plants was associated with two different regions on chromosome 7H. One of the latter genetic windows also explained the variation of RDW of ET- and ABA-treated plants. A sequence homology search was performed to derive the putative function of the genes linked to the QTLs. Several QTLs were identified located close to aphid resistance genes previously mapped. This is the first report of genes associated with hormone response in barley that could be involved with insect resistance. Those recombinant lines carrying the appropriate alleles could be useful for breeding barley to enlarge the genetic base of defence against stress.